ASSESSING PELVIC FLOOR REHABILITATION EFFICACY USING ELECTROMYOGRAPHY - Nargiza Mirkhamidova; Adibakhon Usmankhodjaeva (Central Asian Journal of Medicine, 2024)
Objective: The objective of this research is to assess the efficacy of individualized rehabilitation programs for female sexual dysfunction associated with neurological disorders using electromyography (EMG) to assess the functionality of the pelvic floor muscles. Methods: A total of 133 women with diagnosed sexual dysfunction and various neurological disorders were split into two distinct groups: a control group (n=66) receiving standard care and a treatment group (n=67) undergoing a comprehensive rehabilitation program. This program included transcutaneous tibial nerve stimulation (TTNS), biofeedback therapy and Kegel exercises. EMG was utilized to assess the amplitude and strength of the bulbocavernosus, pubococcygeus, and iliococcygeus muscles prior to and following the intervention. Results: Initial EMG measurements indicated no notable differences between the control and intervention groups (p>0.05), but post-treatment, the intervention group exhibited markedly enhanced muscle function compared to the control group. The mean amplitude (M±SD) of the bulbocavernosus muscle increased from 78.21±7.37 to 132.31±12.72 (p<0.0001), the pubococcygeus muscle from 155.57±14.89 to 254.96±24.82 (p<0.0001), and the iliococcygeus muscle from 77.21±7.37 to 132.78±12.60 (p<0.0001). Conclusion: The results indicate that individualized rehabilitation programs significantly enhance functionality of pelvic floor muscles in women with neurological disorders, as measured by EMG.